2019
DOI: 10.3390/su11061672
|View full text |Cite
|
Sign up to set email alerts
|

Are LEED-Certified Buildings Energy-Efficient in Practice?

Abstract: Depletion of natural resources and climate change are undoubtedly the biggest challenges that humankind faces today. Here, buildings have a crucial role since they consume the majority, i.e., 30% to 40% of the total energy resources. Green building certification is one of the solutions to limit the energy use in buildings. In addition, it is seen to indicate a consideration for sustainability aspects in construction. LEED is the most widely used certificate worldwide. However, recently some critics have raised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 60 publications
(102 reference statements)
1
45
0
1
Order By: Relevance
“…Although different standards have different emphases, they all revolve around the principle of energy saving and emissions reduction [12,13]. However, some buildings selected as green buildings are far from the expected effect [14]. For example, the Bank of American Building, the first office building achieving the LEED Platinum certification in America, consumes a surprising level of energy.…”
Section: Introductionmentioning
confidence: 99%
“…Although different standards have different emphases, they all revolve around the principle of energy saving and emissions reduction [12,13]. However, some buildings selected as green buildings are far from the expected effect [14]. For example, the Bank of American Building, the first office building achieving the LEED Platinum certification in America, consumes a surprising level of energy.…”
Section: Introductionmentioning
confidence: 99%
“…A recent literature analysis analyzes and summarizes studies on this subject. Amiri et al [2]'s search located 164 research papers that covered energy efficiency topics in LEED-certified buildings. Of these, Forty-four peer-reviewed papers were selected and analyzed.…”
Section: Analysis Of the Existing Literaturementioning
confidence: 99%
“…The number of green building certified buildings in Korea, which started in January 2002, has been increasing rapidly year by year [1]. Although the interest in and importance of green building certification have increased, it has been difficult to determine how much less energy consumption is actually used in buildings after obtaining certification [2].…”
Section: Introductionmentioning
confidence: 99%
“…Another important issue is that the majority of the existing LEED-certified buildings are located in the US and Canada [49]. Several studies have been conducted in China, as a developing country, where the number of LEED-certified buildings is increasing.…”
Section: Literature Review On the Costs Of Leedmentioning
confidence: 99%
“…In this case, the efficiency of the building in energy and water consumption besides environmentally-friendly material usage is doubtful. A literature review paper by Amiri et al [49] on the energy-efficiency of LEED-certified buildings revealed that the energy efficiency of LEED-certified buildings, especially at the lower (Certified) level, is questionable.…”
Section: Factual Environmental Performance Of Leed-certified Buildingsmentioning
confidence: 99%